2020
DOI: 10.1021/acssuschemeng.0c03624
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dissolution of Lithium-Ion Batteries Cathode LiCoO2 by Polyethylene Glycol-Based Deep Eutectic Solvents at Mild Temperature

Abstract: With the increasing demand of lithium-ion batteries in recent decades, the growing waste from the electrode materials of lithium-ion batteries has become an urgent problem. Lithium cobalt oxide (LiCoO 2 ), used as the cathode materials of lithium-ion batteries, exhibits high capacity and excellent stability but also a high price. To recycle the LiCoO 2 cathode, it is desirable to develop solvents for the dissolution of LiCoO 2 . At present, the dissolution of LiCoO 2 still requires strong acid or a high temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 41 publications
4
93
0
Order By: Relevance
“…[ 134 ] The strong reducibility of reline enables the extraction at a mild condition (180 °C) with a short reaction time of 12 h. They also found Co can be recycled as Co 3 O 4 using H 2 C 2 O 4 and NaOH precipitants through a dilution–precipitation–calcination process. Other DES systems such as ChCl/citric acid, [ 135 ] p‐toluenesulfonic acid monohydrate/ChCl, [ 136 ] and polyethylene glycol/thiourea [ 137 ] were also studied for the recycling of LiCoO 2 from spent LIBs. In addition to the extraction of metal ions, Wang et al.…”
Section: Dess For Energy Storage Applicationsmentioning
confidence: 99%
“…[ 134 ] The strong reducibility of reline enables the extraction at a mild condition (180 °C) with a short reaction time of 12 h. They also found Co can be recycled as Co 3 O 4 using H 2 C 2 O 4 and NaOH precipitants through a dilution–precipitation–calcination process. Other DES systems such as ChCl/citric acid, [ 135 ] p‐toluenesulfonic acid monohydrate/ChCl, [ 136 ] and polyethylene glycol/thiourea [ 137 ] were also studied for the recycling of LiCoO 2 from spent LIBs. In addition to the extraction of metal ions, Wang et al.…”
Section: Dess For Energy Storage Applicationsmentioning
confidence: 99%
“…In addition to ChCl-based DESs, Chen and coworkers explored a new kind of DES, comprising polyethylene glycol and thiourea (denoted as PEG200/thiourea) with molar ratio of 2:1. [80] In this article, PEG200/thiourea DES was employed for Co leaching purpose. The impact of time on the color change of the DESs/LiCoO 2 solution was conducted.…”
Section: Des A)mentioning
confidence: 99%
“…Likewise, large volume of solid Adapted with permission. [80] Copyright 2021, American Chemical Society. and liquids are generated as primary waste products in the hydrometallurgy.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…suggested that other battery components such as aluminum and copper could serve as reducing agents to enhance the leaching performance of ChCl+citric acid. Recent efforts by Roldán‐Ruiz et al., [11b] Chen et al., [11a] and Wang et al [11d] . demonstrated that varying the hydrogen bond donor types could accelerate the leaching process at mild temperatures.…”
Section: Introductionmentioning
confidence: 99%